Inside Back Cover: Flexible Zirconium Metal‐Organic Frameworks as Bioinspired Switchable Catalysts (Angew. Chem. Int. Ed. 36/2016). Issue 36 (15th July 2016) - Yuan, Shuai; Zou, Lanfang; Li, Haixia; Chen, Ying‐Pin; Qin, Junsheng; Zhang, Qiang; Lu, Weigang; Hall, Michael B.; Zhou, Hong‐Cai
Abstract : Switchable catalysts in flexible MOFs are possible through the inherent cavities and dynamic behaviors of flexible metal–organic frameworks (MOFs), namely the PCN‐700 series, properties that bear a close resemblance to those of regulatory enzymes. In their Communication onpage 10776 ff., W. Lu, M. B. Hall, H.‐C. Zhou, and co‐workers show that manual control of the catalytic properties of these MOFs is possible through reversible pore opening and closing.